Prevalence of xerostomia and its association with systemic diseases and medications in the elderly: a cross-sectional study - Fornari, Cindel Balbinot; Bergonci, Daniel; Stein, Cauane Bruna; Agostini, Bernardo Antonio; Rigo, Lilian (São Paulo Medical Journal, 2021)
BACKGROUND: Dry mouth syndrome or xerostomia is defined as decreased salivary flow or hypofunction of salivary glands. Its origins are multicausal and might be the result of a change in the salivary glands or a systemic imbalance. OBJECTIVE: To ascertain the prevalence of self-reported xerostomia and to identify associated factors. DESIGN AND SETTING: Cross-sectional study on the entire population of 293 elderly people over 60 years of age living in a Brazilian municipality. METHODS: Data were gathered from a questionnaire that asked about demographic data, chronic diseases and use of continuous medications, and which used the Xerostomia Inventory (XI) to evaluate dry mouth sensation. Our analysis consisted of multivariate regression and estimation of odds ratios (OR) and their respective 95% confidence intervals (CI) in binary logistic regression models. RESULTS: The prevalence of self-reported xerostomia was 19.1%. Elderly people with diabetes had higher odds of having self-reported xerostomia (OR: 3.59; 95% CI: 1.48-8.68; P < 0.001) as did those who had chronic diseases and used continuous medication (OR: 2.3; 95% CI: 1.19-4.67; P = 0.009). Elderly people who used continuous medication for the gastrointestinal tract were more likely to have xerostomia (OR: 2.14; 95% CI: 1.03-1.44; P = 0.030). CONCLUSIONS: Elderly people with diabetes and chronic diseases who were using continuous medication were more likely to have dry mouth. Use of continuous medications for the gastrointestinal tract led to a greater chance of having self-reported xerostomia.